Effect of shot peening on notched fatigue performance of powder metallurgy Udimet 720Li superalloy. (August 2021) - Dong, Chengli; Yang, Shengkai; Peng, Zichao
Abstract: The tensile and stress-controlled LCF tests of a powder metallurgy (PM) superalloy, Udimet 720Li have been conducted at 650 °C in order to investigate the effect of shot peening (SP) on notched low cycle fatigue (LCF) performance. The measurements of surface tomography, Micro-Vickers hardness, residual stress and failure mechanism analysis were conducted in detail. The results show that there are many regularly shaped machining traces on as-received (AS) surface while lots of highly disorganized dimples are mainly distributed on SP surface. A larger microhardness gradient is produced along the path from SP surface to the bulk of material compared with AS specimen. The maximum compressive residual stress of SP specimen is not more located at surface like AS one but at a depth of approximately 50–90 μm from surface. Compared with the applied stress, the effective stress curve of SP specimen becomes "flat" and the effective stress gradient decreases accordingly. The LCF lifetime of the notched specimen is significantly improved after SP process and the LCF lifetime increment is between 2.05 and 7.66 times. Finally, there are obvious differences on the failure mechanisms, such as fatigue crack initiation, propagation and final fracture between AS and SP specimens. Graphical abstract: Image 1 Highlights: Notched fatigue tests of Udimet720Li with SP or not are conducted at 650 °C. The highly disorganized shot peening dimples are mainly distributed on SP surface. Larger microhardness gradient is produced near the surface after SP. SP increases residual stress and changes the position of the maximum residual stress. Crack initiation arises from AS surface while that arises from SP subsurface.